PENGEMBANGAN WISATA RELIGI MAKAM RADEN MAS ARIA WANGSAKARA MELALUI PENGUATAN LITERASI DIGITAL - Umar Halim; Anna Agustina; Nurul Hidayat (Jurnal Abdimas Bina Bangsa, 2023)
Indonesia has enormous religious tourism potential and must be developed because religious tourism has a broad economic driving force which has implications for improving the economy and welfare of local communities. One of the potential religious tourism destinations is Raden Mas Aria Wangsakara, who is the founder of Tangerang Regency and also a National Hero. However, this religious tourism is not widely known by the public. The aim of this PkM is to increase public awareness of the potential of religious tourism by promoting social media and improving the digital soft skills of the Lengkong Kulon Village Community. This PkM uses the Participatory Action Research (PAR) method, an approach whose process aims at learning in overcoming problems and meeting the practical needs of society, as well as the production of knowledge and the process of socio-religious change. PKM was carried out from 29 May 2023 to 1 August 2023 in Lengkong Kulon Village, Pagedangan District, Tangerang Regency. The result of this Community Service Activity is the creation of a social media account to provide information on religious tourism and also training to improve soft skills in video editing and content creation